To evaluate the dimensions of each lobe and total volume of thyroid gland by ultrasonography among pregnant and non pregnant women in local population, Karachi. - Hira Ahmed; Shazia Ahmed; Anila Rahim; Khalida Perveen; Talat Saeed; Jahan Ara Ainuddin (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
To evaluate the dimensions of each lobe and total volume of thyroid gland by ultrasonography among pregnant and non pregnant women in local population, Karachi.     Abstract: Background: Pregnancy has an anatomical and physiological influence on the thyroid gland and it's function. It is good to know the normal changes that occur during pregnancy. The size and volume of this gland is increased through the pregnancy and becomes visible due to iodine deficiency (ID) that can lead to goiter or may develop hypothyroidism. Objective of the study were to evaluate dimensions of both lobes and calculation of thyroid volume by using ultrasonography (USG) and to compare these parameters between pregnant and non pregnant in Karachi, Pakistan. Methodology: It was a clinical cross sectional study that was conducted at Gynae OPD and Radiology Department, Ojha campus, Dow university of health sciences (DUHS), Karachi from October 2016 to December 2018 through consecutive sampling. The study volunteers of reproductive age (14-45 years) were included and divided into two groups (pregnant and non-pregnant women). The dimensions of each lobe and calculation of thyroid volume were taken into the account through their standard protocol after following inclusion and exclusion criteria. Results: The comparisons were made on thyroid gland dimensions, ultrasound outcomes of right and left lobe length, width, depth and volume of thyroid gland. In pregnant women, right lobe length was 2.91±1.05, width was 1.54±0.41 and depth was 2.31±1.41 whereas in non pregnant women mean right lobe length was 2.50±0.97, width was 1.34±0.51 and depth was 1.68±0.98. The mean difference was considered statistically significant in pregnant women with p-value (< 0.01). In pregnant women thyroid volume was 7.02±3.21 whereas in non pregnant, it was   5.58±2.41 which was significantly increased in pregnant women with p-value (< 0.01). Conclusion: Therefore our study concludes that, in our population at least half of the apparently healthy pregnant females do have some degree of iodine deficiency. The volume of the gland is increased during pregnancy, suggesting iodine deficiency.   Key Words: Pregnant women, non pregnant women, dimensions of thyroid gland and                       volume of thyroid gland.